Extracurricular Tambourine Management (A Site Study at Madrasah Aliyah Negeri 1 Demak). - Sunarto, Sunarto (2011)
The objectives of this research are to describe (1) to describe the characteristic of membership recruitment on extracurricular tambourine at MAN Demak, and (2) to describe the forms of training process on extracurricular activities at MAN Demak. This is a qualitative research that is conducted in MAN Demak. The human resources in this research are principal, students, teacher and manager of extracurricular tambourine activity. Data collecting technique in this research used observation, interview, and documentation. Data analysis is done by data collection, data reduction, data display, and conclusion. Data validity test used credibility, transferability, dependability, and conformability. The research results show that (1) the recruitment process of rebana extracurricular membership did not need special requirement. All student can be extracurricular that existing in school. The recruitment process of rebana extracurricular membership is started by socialization process by manager of rebana extracurricular activity. The students should registry first to the OSIS management or coordinator of rebana extracurricular on the time that is determined before. In registration process, the student is fulfilling the form to submit their personnel data. Then, the data of students will be re-registration and the result will be patched in the pasteboard. After that the students are given some information about the rebana extracurricular activity. (2) In rebana extracurricular, the practices are done once or twice every week and it is done scheduled and it is done after lesson hour. The practice of extracurricular is done in auditorium or mushola and consorted by 2 builder teacher. But there will be an opportunity to gain the builder teacher if there is needed. The activity of rebana extracurricular is started with warming up activity that is called"senam mulut (mouth gymnastic)" and also moving up their hand. The form of practices that is done in rebana extracurricular activity is made half circle pattern to easies the practices activity.